Kontestasi Politik dan Perimbangan Kekuasaan dalam Perumusan dan Implementasi UU MD3 2014 - Kosandi, Meidi (UI Scholars Hub, 2015)
This paper discusses the politics of policy making behind the signing of the parliamen¬tary institutional arrangement law (UU MD3 2014) from new institutionalism approach. The policy incites controversy over domination of one coalition over the other and the future of legislative-executive inter-institutional relations. This study argues that in the policy making, the drive for power domination in the parliament and the dynamics of contestation in the presidential election strongly affected its process. The absence of convergence and political transactional cost between coalitions pointed us to the lack of relevance of rational choice institutionalism theories in explaining the politics of UU MD3. Although the data shows tendency towards commitment and loyalty to coalition identities, norms and ideas, the historical dynamics of coalition formation during the 2014 general election process indicates the applicability of historical institutionalism more than sociological institutionalism. This study employed discourse analysis on the deliberation in the parliament and opinion and news in the mass media.